Pembuatan Sabun Transparan Berbasis Minyak Kelapa dengan Penambahan Ekstrak Buah Pedada (Sonneratia caseolaris) sebagai Bahan Antioksidan - Sukeksi, Lilis; Destriadi, Ari; Nicholas, Kevin (Talenta Publisher (Universitas Sumatera Utara), 2024)
Mangrove Apple (Sonneratia caseolaris) is a fruit native from tropical area that has antioxidant activity. This study aims to produce transparent soap with pedada fruit antioxidant enhancing agents and the observation of transparent soap quality in accordance with SNI 03-3532-1994 and antioxidant activity of transparent soap. Research began with pre-treatment process, namely extraction of mangrove apple enhancing agent by maceration and infundation method using methanol and water solvent. The obtained extracts were then added as variation of coconut oil soap production formula. The obtained soaps were then tested for free alkali rate, free fatty acid rate, moisture content, foam stability, pH and antioxidant activity by DPPH method. The antioxidant activity of the obtained soap shows that with the formulation by 0.5 g of methanol maceration extract of mangrove apple resulted in soap with IC50 antioxidant activity of 122.30 Î¼g/mL.